Neurospora COP9 Signalosome Integrity Plays Major Roles for Hyphal Growth, Conidial Development, and Circadian Function - Zhou, Zhipeng (Public Library of Science, 2012)
The COP9 signalosome (CSN) is a highly conserved multifunctional complex that has two major biochemical roles: cleaving NEDD8 from cullin proteins and maintaining the stability of CRL components. We used mutation analysis to confirm that the JAMM domain of the CSN-5 subunit is responsible for NEDD8 cleavage from cullin proteins in Neurospora crassa. Point mutations of key residues in the metal-binding motif (EX(n) HXHX(10) D) of the CSN-5 JAMM domain disrupted CSN deneddylation activity without interfering with assembly of the CSN complex or interactions between CSN and cullin proteins. Surprisingly, CSN-5 with a mutated JAMM domain partially rescued the phenotypic defects observed in a csn-5 mutant. We found that, even without its deneddylation activity, the CSN can partially maintain the stability of the SCF(FWD-1) complex and partially restore the degradation of the circadian clock protein FREQUENCY (FRQ) in vivo. Furthermore, we showed that CSN containing mutant CSN-5 efficiently prevents degradation of the substrate receptors of CRLs. Finally, we found that deletion of the CAND1 ortholog in N. crassa had little effect on the conidiation circadian rhythm. Our results suggest that CSN integrity plays major roles in hyphal growth, conidial development, and circadian function in N. crassa.